ChemInform Abstract: Aerobic Synthesis of Pyrroles and Dihydropyrroles from Imines: Palladium(II)‐Catalyzed Intramolecular C—H Dehydrogenative Cyclization. Issue 38 (30th August 2013) - Shi, Zhuangzhi; Suri, Mamta; Glorius, Frank
Abstract The mild cyclization of imines to various pyrrole structures uses molecular oxygen as the sole stoichiometric oxidant.